2000
DOI: 10.14507/epaa.v8n47.2000
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Supply and Demand: Surprises from Primary Research

Abstract: An investigation of primary research studies on public school teacher supply and demand revealed four surprises. Projections show that enrollments are leveling off. Relatedly, annual hiring increases should be only about two or three percent over the next few years. Results from studies of teacher attrition also yield unexpected results. Excluding retirements, only about one in 20 teachers leaves each year, and the novice teachers who quit mainly cite personal and family reasons, not job dissatisfaction. Each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…Across four TFSs from 1988-1989to 2000-2001, Luekens et al (2004 found that attrition was only about 2% higher for public teachers with 1 to 3 years of full-time teaching experience than with 4 to 9 years. We found a similar difference for SETs and GETs separately, with data from the three most recent TFSs.…”
Section: Attritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across four TFSs from 1988-1989to 2000-2001, Luekens et al (2004 found that attrition was only about 2% higher for public teachers with 1 to 3 years of full-time teaching experience than with 4 to 9 years. We found a similar difference for SETs and GETs separately, with data from the three most recent TFSs.…”
Section: Attritionmentioning
confidence: 99%
“…Not all are suited; hence, these should leave (Johnson et al, 2005;NCES, 2005;NCTAF, 2003). And as Wayne (2000) concluded, only one quarter of beginning teachers leave to pursue other careers or because of dissatisfaction. Given these considerations, the somewhat higher rate of 28 attrition for public school teachers with 1 to 3 years of experience is not alarming and some of it is constructive.…”
Section: Benefits Of Turnovermentioning
confidence: 99%
“…The contemporary challenges urban districts face in recruiting and retaining teachers is well-documented (Jones and Sandidge 1997;Darling-Hammond and Sykes 2003), and projected estimates indicate the need for hiring approximately 200,000 new teachers each year into the foreseeable future so as to adequately staff these ''hard-to-staff'' schools (Education Commission of the States 2004 ;Hussar 1999;Wayne 2000). In order to address their staffing needs, urban districts increasingly rely on alternative certification programs designed to provide interested individuals with quick entry into the teaching profession and capitalize upon their greater age, life and work experience, and understanding of urban communities compared to individuals enrolled in traditional teacher education programs.…”
mentioning
confidence: 99%
“…This is especially the case in urban areas where the need for qualified teachers is great but disproportionately high attrition rates amongst beginning teachers contribute to perpetual staffing shortages (Hussar, 1999;Ingersoll, 1997Ingersoll, , 2001Wayne, 2000). For example, teacher turnover in low-income, racial minority schools occurs at rates 50% higher than more affluent, suburban schools (Darling-Hammon & Sykes, 2003).…”
mentioning
confidence: 99%